PENGEMBANGAN MODUL IDENTIFIKASI INSEKTA DI BKPH KEDUNGGALAR KECAMATAN PITU NGAWI PADA MATA KULIAH TAKSONOMI HEWAN INVERTEBRATA - Nur Aini Kusumaningrum (Florea : Jurnal Biologi dan Pembelajarannya, 2015)
Invertebrate taxonomy module courses are limited and textual. Invertebrate taxonomy module that is not based on contextual research. Ngawi Pitu forest can be used as a location for research, because of the diversity of existing invertebrates. The research aims to develop insect identification modules on subjects Taxonomy invertebrate insightful context. Module development using the 4D model (Define, Design, Development, Dissemination). The products produced in the form of modules with product validation to experts and tested on students. The results obtained expert ideals 79 % in both categories. Results of tests on subjects obtained ideals 72% with the good category. The trial results states : 1 ) modules developed well and fit for use with the improvement of writing, 2 ) students easily recognize examples of insects as obtained from the forest and the surrounding environment. Suggestion development need to be large-scale trials to determine the effectiveness of the module as well as need to be developed on a wider material .